1994
DOI: 10.1111/j.1365-4362.1994.tb01037.x
|View full text |Cite
|
Sign up to set email alerts
|

Tinea Capitis in Lahore, Pakistan

Abstract: T. violaceum is the predominant pathogen causing tinea capitis in children and adults in this part of the world and gives rise to a varied clinical picture. Our findings agree with data from other parts of Pakistan and many countries abroad.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
30
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 19 publications
11
30
1
Order By: Relevance
“…This finding was not unexpected since this fungal pathogen has been isolated from cases of human ringworm in different localities of this country [26][27][28][29][30][31]. Our research was based on the analysis of samples originally collected for other purposes, i.e., to investigate skin diseases of parasitic origin in livestock.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding was not unexpected since this fungal pathogen has been isolated from cases of human ringworm in different localities of this country [26][27][28][29][30][31]. Our research was based on the analysis of samples originally collected for other purposes, i.e., to investigate skin diseases of parasitic origin in livestock.…”
Section: Discussionmentioning
confidence: 99%
“…verrucosum infection can be considered to be a cosmopolitan disease as, over time, it has been reported in livestock and sometimes in people in a number of different countries from all continents [5][6][7][8][9][10][11][13][14][15][16][17][18][19][20][21][22][23][24][25]. In Pakistan, several studies have documented the role of this fungal species in human ringworm cases [26][27][28][29][30][31]. However, data are still lacking concerning the animal reservoirs of this fungus.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the similar studies reveal that non-inflammatory types of Tinea capitis were more common (51%) than inflammatory variants (32%) ( Hussain I et al 1994, Kalla G et al 1995, Singal A et al 2001, Jha BN et al 2006). In our study, Seborrhoeic type was more common followed by Black dot and grey patch types., study by Bose et al (2011) and Singal A et al (2001) have reported seborrhoeic variant as the predominant type followed by black dot.…”
Section: Discussionmentioning
confidence: 94%
“…However, in a few cases, it may be characterized by intense inflammation and subsequent cicatricial alopecia, which causes permanent cosmetic disfigurement. Also, the infection is highly contagious and, hence, needs to be recognized and treated early to prevent transmission to siblings and costudents [11][12][13]. Awareness in patients regarding disease was good (88%) and also incidence was higher in urban areas compared to rural population.…”
Section: Discussionmentioning
confidence: 99%